Participation in the classroom as a basis for democracy education? A conceptual analysis of the concept of student participation - Heid, Helmut; Jüttler, Michael; Kärner, Tobias (Frontiers in Political Science, 2023)
In our conceptual analysis, we focus on the concept of student participation and argue for a differentiated consideration of the same. To this end, we elaborate on constituent elements and first address the definitional understanding of the concept considered as well as the participation postulate. Furthermore, we name and discuss possible purposes and qualities of participatory practice and we give an overview of the established conceptualization of participation by means of a stage model and the interdependence of autonomy and heteronomy expressed in this model. We then address participatory fields in the classroom, concrete practices of participatory decision-making, prerequisites and implications of participatory classroom practices, and possible scopes of participatory influence.